(untitled) (Bangladesh Agronomy Journal, 2019)
The experiment was carried out at the research field of Agricultural Research Station, Rajbari, Dinajpur during rabi season of 2014-15 and 2015-16 to find out suitable crop combination for higher productivity and economic return. Six different treatments viz. T1 = Sole brinjal (75 cm x 60 cm), T2 = Sole french bean (30 cm x 10 cm), T3 = Brinjal normal row (100%) + 1 line french bean between brinjal (33%), T4 = Brinjal normal row (100%) + 2 lines french bean between brinjal (66%), T5 = Brinjal paired row (100%) + 3 lines french bean between brinjal (40%) and T6 = Brinjal paired row (100%) + 4 lines french bean between brinjal (53%) were evaluated. The results revealed that the highest mean fruit yield of brinjal (44.26 t ha-1) and french bean (20.96 t ha-1) was obtained in sole cropping of component crops. Under intercropping, the highest brinjal yield (38.61 t ha-1) was recorded in brinjal normal row + 1 line french bean between brinjal, while, the highest french bean yield (16.06 t ha-1) in brinjal normal row + 2 lines french bean between brinjal. The highest mean brinjal equivalent yield (58.72 t ha-1) and land equivalent ratio (1.50) was also obtained in brinjal normal row + 2 lines french bean between brinjal. The highest gross return (Tk. 4,69,760 ha-1), gross margin (Tk. 3,66,440 ha-1), and BCR (4.54) were obtained in brinjal normal row + 2 lines french bean between brinjal and the lowest in sole french bean. The overall results indicated that among the intercrop combinations brinjal normal row + 2 lines french bean between brinjal was found suitable for total productivity and economic return of the system. Bangladesh Agron. J. 2018, 21(2): 1-6